Le Corbusier : ideas and forms - Curtis, William J. R., 1948- (London : Phaidon, 2015)
Originally published in 1996 to critical fanfair, scholar William J.R. Curtis has re-issued his classic text with extensive new scholarship and contemporary research that continues the high standard of the original. Presented chronologically with a clear narrative, Curtis has worked tirelessly not only to document Le Corbusier's key projects in detail but to contextualize them within the architect's overarching philosophy of urbanism and art and the pervading culture of Le Corbusier's time. With full access to the renowned Le Corbusier archive, Curtis' text is lavishly illustrated with new photographs, plans and original sketches and a fresh new design.
Includes bibliographical references and index.
Keywords: Le Corbusier, -- 1887-1965 -- Criticism and interpretation; Architecture, Modern -- 20th century -- France -- Paris; Architecture, Modern -- 20th century; Architecture